2010
DOI: 10.1007/s11999-009-0945-0
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Revision Total Knee Arthroplasty in the United States

Abstract: Understanding the cause of failure and type of revision total knee arthroplasty (TKA) procedures performed in the United States is essential in guiding research, implant design, and clinical decision making in TKA. We assessed the causes of failure and specific types of revision TKA procedures performed in the United States using newly implemented ICD-9-CM diagnosis and procedure codes related to revision TKA data from the Nationwide Inpatient Sample (NIS) database. Clinical, demographic, and economic data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
590
1
23

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,101 publications
(659 citation statements)
references
References 24 publications
18
590
1
23
Order By: Relevance
“…Infection is currently the most frequently reported reason for revision in TKA [3]. However, the current risk of infection as well as the relative importance of various risk factors remains under debate as a result of the rarity of the complication, changes in the treatment and prevention of infection over time as well as the practical difficulties associated with conducting well-controlled clinical studies on this topic with long-term followup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection is currently the most frequently reported reason for revision in TKA [3]. However, the current risk of infection as well as the relative importance of various risk factors remains under debate as a result of the rarity of the complication, changes in the treatment and prevention of infection over time as well as the practical difficulties associated with conducting well-controlled clinical studies on this topic with long-term followup.…”
Section: Discussionmentioning
confidence: 99%
“…In light of our longitudinal analysis of the incidence of PJI in the Medicare patient population, along with other followup studies [17] and cross-sectional analysis of national hospitalization records [3], emphasis should be placed on minimizing the risk of PJI after primary TKA. Because PJI is a challenging complication for patients, hospitals, surgeons, and payers [4], effective strategies such as stringent patient screening for risk factors or adequate antibiotic prophylaxis [17] should be developed and implemented to combat this complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection is a leading cause for revision total knee arthroplasty (RTKA) [11,12]. Studies have shown that 6.6% to 38% of RTKAs are attributable to prosthetic knee infections [5,11,23,24,31,41,43,55,58,76,95,96].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 6.6% to 38% of RTKAs are attributable to prosthetic knee infections [5,11,23,24,31,41,43,55,58,76,95,96]. Although some [56,63] prefer it, a two-stage procedure for chronic prosthetic knee infection requires temporary cement spacers to preserve limb length and reduce soft tissue retraction.…”
Section: Introductionmentioning
confidence: 99%